2021
DOI: 10.3389/fnagi.2021.772036
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Antioxidative Stress Therapy Research for Early Brain Injury After Subarachnoid Hemorrhage

Abstract: The main reasons for disability and death in aneurysmal subarachnoid hemorrhage (aSAH) may be early brain injury (EBI) and delayed cerebral ischemia (DCI). Despite studies reporting and progressing when DCI is well-treated clinically, the prognosis is not well-improved. According to the present situation, we regard EBI as the main target of future studies, and one of the key phenotype-oxidative stresses may be called for attention in EBI after laboratory subarachnoid hemorrhage (SAH). We summarized the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 193 publications
0
13
0
Order By: Relevance
“…Too few studies might lead to an overestimation of the efficacy of RES. Besides, many studies suggested that 24 h after SAH is the optimum time point to complete the pathological and functional detection of EBI in animals ( Lin et al, 2021 ). Therefore, normalizing the selection of the observation point needs to be performed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Too few studies might lead to an overestimation of the efficacy of RES. Besides, many studies suggested that 24 h after SAH is the optimum time point to complete the pathological and functional detection of EBI in animals ( Lin et al, 2021 ). Therefore, normalizing the selection of the observation point needs to be performed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, researchers began to pay attention to the new mechanism of nerve injury caused by SAH. Currently, the research on the mechanism of poor clinical prognoses caused by SAH mainly focuses on early brain injury (EBI) and delayed brain injury (DBI) [ 34 , 35 ]. In particular, EBI is considered to be the main reason for the poor outcomes in patients after SAH [ 34 , 36 , 37 ].…”
Section: Research Progress In Poor Prognosis After Sahmentioning
confidence: 99%
“…Post-SAH EBI refers to any acute pathophysiological events that occur in the brain within 72 h after SAH, such as brain cell death, blood–brain barrier destruction, cerebral edema, oxidative stress, neurological deficits, acute vasospasm and impaired brain autoregulation [ 34 , 38 ]. In contrast to EBI, DBI refers to the pathophysiological event in brain tissue 72 h after SAH, which is mainly caused by delayed cerebral vasospasm (DCV) [ 39 , 40 ].…”
Section: Research Progress In Poor Prognosis After Sahmentioning
confidence: 99%
“…Redox homeostasis regulates the normal physiological functions of cells. Excessive free radicals can exhaust the intrinsic antioxidant system, resulting in lipid peroxidation, DNA damage, and protein breakdown [ 11 ]. Ferroptosis is a new regulated cell death induced by excessive free radicals [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sirtuin 1 (SIRT1) is a well-known epigenetic regulator that modulates gene transcription and impacts various biological functions, such as oxidative stress, inflammatory response, and mitochondrial biogenesis [26]. Numerous studies have shown that SIRT1 has a great antioxidative capacity and plays a neuroprotective role against EBI after SAH [11]. SIRT1 activation mitigates the oxidative stressinduced EBI by inhibiting p53-and nuclear factor-kappa B-(NF-κB-) mediated oxidative pathways and upregulating the nuclear factor-erythroid 2-related factor 2 antioxidant pathway [27][28][29].…”
Section: Introductionmentioning
confidence: 99%